The role of platelets in the pathogenesis of and immunity to helminth infections - Pollock, Jonathan (Department of Pathology, 2023)
Background: Platelets are small, anucleate cells which circulate in blood and are often the first to respond to tissue damage and vascular inflammation caused by pathogens. Here they not only maintain tissue integrity and prevent bleeding, but also initiate and regulate a vast variety of immunologic responses. Little is known on the role of platelets in helminth infections, despite our understanding that many helminth species cause significant vascular pathology as they transfer from the circulatory system to diverse tissues as part of their life cycles. Based on previous studies showing tight association between platelets and innate immune responses during infection with other pathogens, we hypothesized that platelets significantly contribute toward acute (vascular) immunity to helminth infection. Objectives: This project aimed to investigate the role of platelets in regulating acute innate immune responses following infection with the murine gastro-intestinal nematode N. brasiliensis (Nb), commonly used to model human helminthiases. Specifically, it aimed to characterized plateletregulated responses involved in acute innate immunity during the pulmonary stage of infection, in which larvae exit the pulmonary vasculature and invade host lung tissue. Methods: C57BL/6mice were infected with 500 L3 Nb larvae, and the association of platelets with acute innate immune responses in the circulation and the lung were established by flow cytometry and immunohistochemistry. In further experiments, mice were depleted of their platelets using antibodies prior to infection with Nb and the effect of this on pulmonary pathology and innate immune responses was inferred from flow cytometric and histologic analyses of pulmonary tissues. Lastly, antibodies were used to interfere with platelet receptors during Nb infection to gain mechanistic insight into platelet regulation of neutrophil responses. Results: Infection with N. brasiliensis was associated with significant changes in the activation of platelets, their localisation into lung tissue and their interaction with innate immune cells. Additionally, platelet -immune cell interaction was associated with changes in the expression of factors known to play a role in driving the early immune response to Nb, including IFN-γ and RELMα. Furthermore, mice depleted of their platelets prior to infection had significantly enhanced pulmonary pathology and rapidly succumbed to infection. This was associated with significant changes in neutrophil responses, and depletion of neutrophils together with platelets significantly protected against enhanced pathology. Finally, direct and indirect targeting of the platelet receptors CD62P and CLEC-2 did not result in significantly enhanced pulmonary pathology but was associated with altered platelet and neutrophil responses. Conclusion: Herein, we have provided evidence that platelets tightly associate with protective host responses during acute N. brasiliensis infection and that their absence correlates with a dysregulated neutrophil response and enhanced helminth – associated pulmonary pathology. These data therefore collectively show that platelets play notable roles in the acute innate immune response to N. brasiliensis and that future investigations into the immunological functioning of platelets during helminth infection are warranted.